Validitas dan Reliabilitas Skala Psikologis Percaya Diri untuk Mengukur Tingkat Percaya Diri Siswa SMK Kota Kediri - Krisphianti, Yuanita Dwi; Nora Yuniar Setyaputri; Galang Surya Gumilang (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2020)
Self confidence is a beliaef that exists in individuals that is able to behave as what is needed in order to get results in accordance with what is needed in order to get results in accordance with what is expected. The form of confidence is shown by; believe in personal abilities, independent, positive self-concept, show up personal opinions. Self confidence is important in personality of SMK students, because SMK education preparing students to enter the workforce and developing professional attitudes. The purpose of this study is to increase self confidence of SMK students in Kediri by using the GURU Process. The validity and reliability is important instruments is carried out to obtain accurate and accountable data in order to determine the level of confidence of SMK students in Kediri. This article is limited just results of validity and reliability from this scale. Based on the results of the validity test distributed to 50 students, 21 valid items with a reliable coefficient of 0.814. Based on the validity and reliability test of the instrument, this scale can be used to measure the self confidence of SMK students in Kediri at the next research stage. Key Word: psychological self confident scale, self confident, GURU process